1988
DOI: 10.1136/bmj.297.6655.1017
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of gastroduodenal damage induced by non-steroidal anti-inflammatory drugs: controlled trial of ranitidine.

Abstract: Objective-To evaluate the prophylactic effect of ranitidine 150 mg twice daily in patients requiring one of the following non-steroidal anti-inflammatory drugs: naproxen, piroxicam, diclofenac, and indomethacin. In addition, risk factors were studied in order to help in targeting of such treatment to specific groups of patients.Design-Double blind, placebo controlled, randomised, parallel group with endoscopic assessments at 0, 4, and 8 weeks.Setting-Multicentre outpatient study at secondary referral centres i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
118
1
4

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(124 citation statements)
references
References 36 publications
1
118
1
4
Order By: Relevance
“…52 Moreover, the protective effect of histamine H 2-blockers seen in RCTs have not translated well into clinical use. 52,53 For example, a recent study shows that using histamine H 2-blockers to suppress tNSAID-induced dyspepsia can double the risks of serious gastrointestinal bleeding. 51 However, this was an observational cohort study and there may be other confounding factors responsible for the gastrointestinal effects.…”
Section: Successive Celecoxib Efficacy and Safety Study I (Success-i)mentioning
confidence: 99%
See 1 more Smart Citation
“…52 Moreover, the protective effect of histamine H 2-blockers seen in RCTs have not translated well into clinical use. 52,53 For example, a recent study shows that using histamine H 2-blockers to suppress tNSAID-induced dyspepsia can double the risks of serious gastrointestinal bleeding. 51 However, this was an observational cohort study and there may be other confounding factors responsible for the gastrointestinal effects.…”
Section: Successive Celecoxib Efficacy and Safety Study I (Success-i)mentioning
confidence: 99%
“…50,51 Histamine H2-blockers decrease the incidence of dyspepsia in patients using tNSAIDs, but at standard doses they appear to have little or no effect on the gastric lesions. 52 Moreover, the protective effect of histamine H 2-blockers seen in RCTs have not translated well into clinical use. 52,53 For example, a recent study shows that using histamine H 2-blockers to suppress tNSAID-induced dyspepsia can double the risks of serious gastrointestinal bleeding.…”
Section: Successive Celecoxib Efficacy and Safety Study I (Success-i)mentioning
confidence: 99%
“…Three studies recruited participants with Lanza scores of zero (undamaged GI surfaces). 48,49,57 One study only recruited patients with normal gastric mucosa. 46 One study recruited people with no more than one or two erosions or haemorrhages.…”
Section: Participantsmentioning
confidence: 99%
“…(which parenthetically had repeatedly been shown to be ineffective for NSAID ulcer prevention) 4 and to half-dose misoprostol (200 lg b.d.) (equivalent to approximately 600 mg of cimetidine as an antisecretory drug).…”
mentioning
confidence: 99%
“…We also found it ironic that Dr Graham suggested that industry support indicates that we were 'willing, trusting, and possibly naïve' tools of the study's sponsor. Review of Dr Graham's publications in the past 2 years reveals four articles assessing medications 1-3 or a diagnostic test 4 for which support was provided by the manufacturer of the product. Most articles published as guidelines, even those of the US national GI organizations, are not properly developed guidelines, but rather reviews by an author or authors who then make recommendations based on the results of their review.…”
mentioning
confidence: 99%